PENEGAKAN KODE ETIKA PROFESI KPK - Firgilius Kandro Mego Asman; Pregrinus Rangga, Dwityas Witarti Rabawati (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
With the rise of corruption cases, law enforcement officers who should be able to actualize legal norms actually experience malpractice in the legal profession. There are 5 (five) ethical pillars of the Corruption Eradication Commission, namely Religiosity, Integrity, Justice, Professionalism and Leadership, in enforcing them there is a need to measure the extent to which the Corruption Eradication Committee can carry out its role in implementing these principles. This qualitative research is normative research, namely by examining literature books, legislation and other written materials. The results of the research, in reality, there were several cases of violations of the code of ethics. And the occurrence of several cases at the Corruption Eradication Commission shows that there has been a failure in this profession. The conclusion is that, the existence of a code of ethics for the legal profession is an important and closely related part of regulating the behavior of the Corruption Eradication Commission as an embodiment of good and fair law enforcement.